How SMEs respond to legal requirements to provide information, training, instruction and supervision to workers about work health and safety matters. (July 2019) - Bluff, Elizabeth
Highlights: OHS laws require provision of information, training, instruction and supervision. SMEs use passive knowledge exchange, and basic checks on safe work practices. Most SMEs provide limited ITIS in an ad hoc way. Planned interventions using participative methods would be more effective. SMEs need guidance to implement flexible legal requirements for ITIS. Abstract: In many countries, laws for work health and safety (WHS) require employers to provide information, training, instruction and supervision (ITIS) to their workers about WHS matters. The objective of this study was to investigate how small and medium enterprises (SMEs) provide ITIS in the context of Australia's model WHS laws. The study was conducted in 46 SMEs, in three industries (construction, manufacturing, and health care and social assistance). Data about ITIS were collected primarily through interviews and documentation review, and supplemented by observation of work. The thematic analysis of data distinguished SMEs' main methods for providing ITIS ('methods'), and their approach to, and the scope of, their ITIS provision ('performance'). The literature about ITIS provision was applied in characterising SMEs' methods and performance. The methods generally involved passive knowledge exchange, and basic supervision to check safe work practices, rather than engaging and participative methods. However, some SMEs' methods included easy to understand information, and opportunities to learn in different ways. Most SMEs, including all small enterprises, provided limited ITIS in an ad hoc way. Only a small number of enterprises, all medium, used a carefully considered and substantial mix of methods. Within each of the three industries, SMEs favoured particular methods due to industry–specific influences. The study raises questions for WHS policy makers and practitioners about the translation of flexible, non-prescriptive legal requirements into workplace practice, particularly in small enterprises. Therefore, options are canvassed for guidance about developing and implementing ITIS initiatives, or engaging external providers for these.